Pragmatic Analysis of Deixis in SBY’s Speech upon Accepting the World Statesman Award - Dwi Maryani Rispatiningsih (Budapest International Research and Critics University, 2021)
Susilo Bambang Yudhoyono is the president of Indonesia. He quite famous in the world. It is proved by award that he got as the world statesman conferred by the appeal of conscience foundation in May 29, 2013. This research analyzes deixis in pragmatic point of view on SBY’s speech upon accepting the world statesman award. The data for this research is in form of speech brows from online websites. This research applies a qualitative research. The result of SBY speech show that, he more often person deixis, it show 55 (74%) times, while others, he only use 10 times (14%) for place deixis and 9 (12%) for time deixis. In personal deixis, SBY most use 1st person plural (63.6%) in his speech, that is the word we and our, both of them refer to Indonesian. Thus, in his speech, he represents his self as Indonesian. It is also shown by using of proximal place (80%) along the speech. For time deixis, he more use present tense (45%) because he talk about the event that happens when speech is delivered.